PROPHETIC TRADITIONS AND THEIR RELEVANCE TO ECOLOGICAL BALANCE IN THE MODERN ERA: A MUST REFLECTION IN MUSLIM DAILY LIFE - Kusumaningtyas, AD; Sofwan Hadi, MA; Fahmi Rizal, M (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
In our situation nowadays, we often see in our daily life some ironical phenomena. On one side, we see some people who are very excessive in their lifestyle such as flexing, being greedy on foods as shown by some phenomena as ‘mukbang’ including wasting foods’ during ifthar at Ramadhan or in some religious ceremony; on the other hand we also meet some phenomena that are popular with some names ‘rojali, rohana, and roh halus’ (rombongan jarang beli, rombongan hanya nanya, dan rombongan hanya elus-elus) which describes our economic crisis in this era. Also we also see some phenomena such as wasting the water after ablusion (wudhu) in the mosque and prayer room; while some other people were experiencing some watersource drougt. Or in another case, there were some Arabic written such as “an nadhafatu minal iman” in some religious places, but we still see some people do not throw the garbage correctly so that it cause some floods in many places. These are most questionable phenomena which should be reflected in the recent era on: 1) How does the hadith of the Prophet not always bring the prophetic traditions in the muslim lifestyle, and 2) Does it bring the relevancy to the ecological balance in the modern era? This short paper hopefully can analyse this phenomena.